Legal and bioethical issues of interventions and research in persons with intellectual disability in Chile - Muñoz Quezada, María Teresa; Lucero Mondaca, Boris Andrés (Acta Bioethica, 2014)
This article presents a review and discussion of ethical and legal issues which protect subjects with intellectual disability in their participation in research or therapeutic interventions in Chile, moreover reflecting on situations of diagnosis and treatment which generate conflict with respect to the rights of persons with intellectual disability. The specific topics are linked to autonomous decision and capacity in informed consent, the rights of persons with intellectual disability, the evaluation of capacity and the reflection on some bioethical dilemmas in the treatment and evaluation of intellectual disability. The following is proposed: to recognize the rights of persons with intellectual disability to decide by themselves and the recognition of equal rights and opportunities to develop procedures and protocols standardized and adapted for cultural diversity in the country for evaluating capacity. Furthermore, caretakers, family members and professionals should consider not only regulations for research and treatment, but also the opinion and decision of persons with disabilities and inform them about such experiences considering their individual characteristics.